Narrative analysis of character Po’s identity crisis in Kung Fu Panda 3 - Setiadi, Raymond Victor; Indriani, Sri Seti; Puspitasari, Lilis (ProTVF, 2025)
Background: Kung Fu Panda 3 is an animated film from the United States that collaborated with a Chinese company. The film tells the story of Po's journey in handling his identity crisis as the main antagonist threatens the village's peace. Addressing social issues such as identity crisis, this animated film, a combination of action and comedy genres, is considered interesting to research as the presence of identity crisis issues is relatively unnoticed among people of different ages. Purpose: This research aims to provide the process of Po's character in handling their identity crisis throughout the story of Kung Fu Panda 3. Methods: This research uses a qualitative research method using narrative analysis by Tzvetan Todorov, which is supported by the approach of Lacey and Gillespie. Results: This research’s findings depict the process of Po's character in resolving its identity crisis whilst overcoming the menace from the villain, which is analyzed according to the five stages of narrative structure in Tzvetan Todorov's narrative analysis method with the approach of Lacey and Gillespie. Scenes are classified into five stages: equilibrium, disruption, recognition of disruption, attempt to repair disruption, and reinstatement of equilibrium. Conclusion: This research concludes with an overall representation of how the character Po can overcome their identity crisis through the five stages and suggests a utilitarian application of a thorough narrative analysis from a communication perspective. Implications: This research can theoretically serve as to how identity crises arise and are resolved in people with the role of other individuals around them in communications. Directors and scriptwriters, especially those producing animated films, can use this research to communicate issues on mental health in a way that people can perceive easily and have fun.